Tingkat Kesadaran Mahasiswa/I terhadap Penggunaan Kosakata yang Sesuai dengan KBBI - Ivo Elsa Hutabarat; Jistisya Maria Tarigan; Servina Indah Yani Tarigan; Selfiana Hanson Pangaribuan; Sesil Audia Br Sibarani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Indonesian, as the official and academic language in Indonesia, has linguistic standards outlined in the Kamus Besar Bahasa Indonesia (KBBI). However, in practice, the use of vocabulary that aligns with KBBI is still not a common habit among university students. This study aims to review students' awareness of using vocabulary that conforms to KBBI and the factors influencing it. The method used in this research is a literature review, analyzing various sources, including academic journals, books, and relevant articles. The findings indicate that students' awareness of using standard language remains low due to social environment influences, social media exposure, and a lack of emphasis on formal language use in academic learning. Additionally, the habit of using informal language in daily communication, particularly on digital platforms, is one of the primary reasons for the decline in formal language quality among students.